STRUKTUR DAN KINERJA INDUSTRI KERTAS DAN PULP DI INDONESIA: SEBELUM DAN PASCAKRISIS - Fitri Wulandari (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This research is intended to describe how concentrate of industrial market of pulp and paper before and after crisis was occur, and to analyze how impact of structure to pulp and paper industrial performances before and after crisis. Method being used in this research is concentration ratio (CR) either CR4 or CR8. This research is also uses multiple regression to see impact of independent variables (market share, cost of capital, efficiency and cost of raw material) to dependent variable (added value). The results of research are concentration ratio (CR) of total raw material, CR of added value, and CR of output; all of those are increase both CR4 and CR8. This means that crisis have had impact toward increasing concentration ratio pulp and paper industries, whereas CR of wage is decrease. CR4 decrease by 13% and CR8 decrease by 14%. The results of this research also indicate that cost of capital have negative impact to added value of company. Companies whose have less capital would have higher profit, vice versa. Cost of raw material has negative impact on company’s profit. Market share has positive impact on company’s profit.